Albistyla, a new genus of Neotropical Limosininae (Diptera: Sphaeroceridae) - Marshall, Stephen A. (Zootaxa, 2014)
The genus Albistyla is described for a group of similar, highly distinctive Neotropical species that key out at couplet 55 of the key to Neotropical Sphaeroceridae in Marshall and Buck (2010). Albistyla is diagnosed by the combination of a single pair of strongly cruciate interfrontal bristles, two dorsocentral bristles, and the costa ending at the tip of R4+5. It is defined as a monophyletic group primarily on the basis of the unusually modified male sternite 5 and the distinctive white surstylus with broad apical scales. The genus is infrequently collected and only the type species is known from good series. Many of the specimens examined were taken in association with tree falls or similar habitats rich in green leaf litter.